Hambatan Pembelajaran Berbasis Web di Indonesia - Ismi Solikhatun; Denies Priantinah (Edunusa: Journal of Economics and Business Education, 2021)
The study aims to highlight opportunities and implementation of web-based learning barriers in Indonesia. The study is a systematic review. The stage of this study uses Chitu Okoli model where the stage is planning, selection, extraction, and execution stage. Web-based learning offers great opportunities to gain access for unlimited learning, flexibility, using collaborative learning, visual language that is more interesting, integrates a variety of learning, increases the ability of independent learning, facilitates control of student activities, and saves lower costs. Nevertheless, web-based learning has challenges. In Indonesia, web-based learning lack of economic gap, iliteracy digital, difference in school infrastructure, teacher competencies, learning environments, student motivation, curriculum and the role of government as policy makers in providing regulation and policy. Although new cultural learning arises from formal and informal learning in the online (web) world, it does not directly negate traditional school-based learning. The results study are expected to be used as consideration of policy makers in making regulations and rules about web-based learning and making a curriculum that is adapted to biases and opportunities.